IMPLEMENTASI STRATEGI MEMBACA 3 P (PERLUAS JANGKAUAN MATA, PERCEPAT GERAK MATA, DAN PERKECIL REGRESI) DI SMA NEGERI 1 NGORO - JOMBANG - Hariyati, Nuria Reny (Balai Diklat Keagamaan Surabaya, 2016)
The objectives of this study are to find out :(1) the influence of theexpanded view of the eyes on speed and understanding readingcapability, (2) the influence ofthe acceleration of the eyeballmovement on speed and understanding reading capability, (3) theinfluence ofthe reduction of eye regression patterns on speed andunderstanding reading capability. The hypothesis of this research isthat 3—perpattern has significant influence on speed readingcapability. This study is qualitative approach using quasi experimentalwith Times-Series Design with Control Group model. The data ofthis study were on the students’ score of reading speed and thescore on reading comprehension. The research population werestudents of grade X! SMAN 1 Ngoro Jombang. The decision ofstudents used purposive sampling techniques, the control groupwere students of XI IPA1 dan Experiment group were students of XIIPA 2.The instruments of this study were the instrument form and tryout of the instrument and analyzed using Ancova. The result showedthat the hypothesis were accepted. 3 P pattern influenced significantlyon the capability of reading speed and understanding the level ofsignificance is 0.05. This research recommended that the teachershould implement 3 P in reading lesson plan, and the teacher shouldgive the 3 P pattern treatment in speed reading learning.